TECHNICAL APPLICATIONS FOR DETERMINING THE FOOT OF THE CONTINENTAL SLOPE POINTS UNDER THE ARTICLE 76 OF THE UNITED NATIONS CONVENTION ON THE LAW OF THE SEA, 1982 - Tuan, Tran Anh (Vietnam Journal of Marine Science and Technology, 2012)
For determining the outer limits of the extended continental shelf, the identification of the foot of the continental slope (FOS) points are very important because they are the basis for computing two formula for determination of outer limit lines such as the continental slope plus 60 nautical miles line (Hedberg formula line) and the 1% sediment thickness line (Gardiner formula line). These are two formula lines used to determine the outer limits of extended continental shelf. This paper will focus on engineering applications in the identification of the continental slope points based on the paragraphs in the Article 76 of the United Nations Convention on the Law of the Sea, 1982 (UNCLOS 1982).